Tehran University students\' knowledge about sexually transmitted disease - fatemeh rahmatinajar klaie (Journal of Holistic Nursing and Midwifery)
Introduction: Sexually transmitted diseases (STD) such as gonorrhea, syphilis and ‎trichomonias are the most common infection disease in the world. Since young adults are at ‎substantial risk for contracting STD and previous studies have shown youth poor knowledge ‎level.‎